PENGARUH KEGIATAN KEAGAMAAN TERHADAP KEPRIBADIAN MUHSIN SISWA KELAS VIII DI MTS MISYKAT AL-ANWAR KWARON JOMBANG - Nur Sholihah, Lisa; Said, Ali; Hijriyati, Muthi’ah (Education, Learning, and Islamic Journal, 2020)
Religious activities on personality are very continuous, we know that by doing religious activities will form a good personality. As is the case with prayer, that there is a significant correlation between the vertical dimension and the horizontal dimension, which means that the better the individual's spirituality level towards God, the better his social behaviour. Such is the case at Madrasah Tsanawiyah Terpadu Misykat Al-Anwar Kwaron Jombang which has implemented religious activities. The application of religious activities is due to the decreasing number of student ethics among adolescents. This has become a researcher's interest to find out more about the influence of religious activities on student personality. This study aims to determine how much influence the implementation of religious activities has on student personality. This study uses a quantitative approach, the study design uses ex post facto and correlational types. Data collection techniques consisted of documentation and questionnaires. In this study, the data analysis used the product-moment, Cronbach's alpha and Spearman rank with SPSS 16. Based on the results of the Spearman rank test, the obtained sig was 0.000, which means that Ha is accepted and H0 is rejected, which means that there is a positive and significant influence between the variables. religious activities and student personality. In the column the correlation coefficient between religious activities on student personality is 0.681, which is between the values of 0.600 - 0.799, this means that it has a strong influence.